Comparative Diagnosis of Alveolar Antral Wall in the Maxillary Sinus Wall in Corresponding OPG, CBCT, MRI-A Radiographic Comparative Study - Ankita Pati; Dhaval Charan; Pooja Mahay; Niva Mahapatra; Ankur Bhagat; S. Bhuvaneshwari (Journal of Pharmacy and Bioallied Sciences)
Introduction: This study compares the efficacy of orthopantomography (OPG), conebeam computed tomography (CBCT), and magnetic resonance imaging (MRI) in diagnosing the alveolar antral artery (AAA) within the maxillary sinus. Materials and methods: Conducted among 297 patients in Odisha, with ages ranging from 20 to 50 years, the study utilized three observers to ensure reliability. Results indicated that MRI is the gold standard for AAA visualization, with high intraand interobserver reliability (Cohen’s kappa = 1.0). Results: OPG offers minimal radiation exposure and CBCT provides detailed 3D bone imaging, MRI excels in soft tissue contrast without radiation, proving essential for accurate diagnosis and surgical planning.